Qualitative analysis of a model for co-culture of bacteria and amoebae - Laura Fumanelli; Pierre Magal; Dongmei Xiao; Xiao Yu (Mathematical Biosciences and Engineering)
In this article we analyze a mathematical model presented in[11]. The model consists of two scalar ordinarydifferential equations, which describe the interaction betweenbacteria and amoebae. We first give the sufficient conditions for theuniform persistence of the model, then we prove that the model canundergo Hopf bifurcation and Bogdanov-Takens bifurcation for someparameter values, respectively.